The Effect of Work Environment and Reward on Employee Engagement: Palmerah Urban Village, West Jakarta - Firda Rahmawati (Universitas Mercu Buana, 2021)
Urban Village is part of the government service office, especially the West Jakarta government. The main task of the government apparatus is to serve the people. The good and bad services provided by the apparatus will reflect the individual performance which will determine the good and bad performance of the organization as a whole. In this study the authors conducted research to determine what factors influence employee engagement in Palmerah Village. The purpose of this study is (1) to analyze the effect of work environment on employee engagement (2) to analyze the effect of reward on employee engagement. This type of research is quantitative. The sample of this research is 93 employees who work in the village of Palmerah. Through the path analysis of PLS version 3.0, it can be concluded that (1) the work environment has a positive and significant effect on employee engagement (2) rewards have a positive and insignificant effect on employee engagement. The implication of the results of this study is that it is necessary to maintain employee engagement in the Palmerah village will increase.